(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: To evaluate the knowledge, attitude and practice of dental educators on virtual reality based technology in dental educationIntroduction:-Virtual reality is another and a very reforming idea and its encouragement in the field of clinical analysis is taking this innovation to another level. Test systems of computer generated reality give fundamental fitness for planning in a controlled area, working patients liberated from pressure without management.Materials and methods:-A questionnaire was prepared with all the questions regarding this study. The survey was circulated on the online platform to 100 teaching faculty in the college. statistical analysis was done using SPSS software. p<0.05 was considered statistically significant.Results:-There is a need to understand the importance of virtual reality and its application in the field of dentistry. It is found that 78% of the population are aware of the new technology and machines , p=0.346 .Conclusion:- The trendsetters in medical VR will be entitled to refining technical efficiency and increasing physical and psychological comfort and capability, while keeping an eye to reducing costs for healthcare.